Airport planning and management - Young, Seth B.; Wells, Alexander; McGraw-Hill eBooks (New York : McGraw-Hill, 2014)
"The definitive, up-to-date guide to airport planning and management. Fully revised, updated, and reorganized to reflect the latest advances in the aviation industry, Airport planning and management, sixth edition offers comprehensive coverage of this challenging field. Airports, airport systems, operations management, and administration are discussed in detail. This authoritative volume addresses changes in technology, structure, and political environment, including enhanced security, environmental impact, and regulatory issues. The Sixth Edition of this landmark guide to the planning, development, and management of airports is ideal as a course text, self-study tool, and professional reference. Coverage includes: Introduction to airports and airport systems, Airport and airport systems: organization and administration, Historical and legislative perspectives, The airfield Airspace and air traffic management, Airport operations management under FAR Part 139, Airport terminals and ground access, Airport security, Airport financial management, Economic, political, and social role of airports, Airport planning, Airport capacity and delay, The future of airport management"--Provided by publisher.
"Airport planning and management, sixth edition offers detailed coverage of all of the advancements the aviation industry has experienced in the nearly seven years since the previous edition was published. These include the latest cutting-edge technologies; crucial changes to a variety of rules, regulations, and policies; essential security measures; and reactions to geopolitical events. This is the most authoritative, up-to-date, and comprehensive resource on the topic"--Provided by publisher.
Airports and airport systems: an introduction -- Airports and airport systems: organization and administration -- Airports and airport systems: a historical and legislative perspective -- The airfield -- Airspace and air traffic management -- Airport operations management under 14 CFR Part 139 -- Airport terminals and ground access -- Airport security -- Airport financial management -- The economic, political, and social role of airports -- Airport planning -- Airport capacity and delay -- The future of airport management -- Code of federal regulations: 14 CFR: aeronautics and space, parts 1 through 199: federal aviation regulations -- Code of federal regulations: 49 CFR: transportation, 1500 series: transportation security regulations -- Federal aviation administration 150 series advisory circulars -- Phonetic alphabet.
Print version c2011.
Also issued in print.
Description based on cover image and table of contents, viewed on March 21, 2014.
Keywords: Airports -- Planning; Airports -- Management; Airports -- Design and construction; Air traffic control; Airports -- Forecasting; Aeronautics -- Law and legislation -- United States; Electronic books